Genome Wide Differential Expression Profiles in Nevus Sebaceous Uncovered Low Expression of CDKN2AIP and Construction of a ceRNA Network - Yang X; Qiao R; Ni N; Zhang Q; Zhang K; Shao X; Cheng W; Sun J; Jiang Y (Dove Medical Press, 2022)
Xianhong Yang,1 Rui Qiao,1 Nana Ni,1 Qian Zhang,2 Ke Zhang,2 Xuebao Shao,1 Wei Cheng,1 Jianfang Sun,1 Yiqun Jiang1 1Department of Dermatopathology, Institute of Dermatology, Chinese Academy of Medical Sciences and Peking Union Medical College, Nanjing, 210042, People's Republic of China; 2Department of Surgery, Institute of Dermatology, Chinese Academy of Medical Sciences and Peking Union Medical College, Nanjing, 210042, People's Republic of ChinaCorrespondence: Yiqun Jiang; Jianfang Sun, Email yiqunjiang@qq.com; sunjf57@163.comBackground: Nevus sebaceous (NS) is a benign hamartoma of the skin, characterized by hyperplasia of the epidermis, in addition to immature hair follicles. The exact mechanisms of folliculo-sebaceous-apocrine defects and adnexal tumorigenesis are unknown in NS, but benign and malignant neoplasms are often due to a complex etiology in NS. Long noncoding RNAs (lncRNAs) have been implicated in various important biological processes and regulate inflammatory diseases and tumors. However, the role of lncRNAs in nevus sebaceous is unclear.Objective: To identify NS-associated mRNA and lncRNA profiles and predict their potential roles in the development of the folliculo-sebaceous-apocrine unit and adnexal tumorigenesis.Methods: RNA-seq was used to identify NS-associated genes and lncRNAs. Analysis software Illumina NovaSeq 6000 was used to analyze the sequences, and real-time PCR and Western blot were used to validate the differentially expressed genes. Competing endogenous RNAs (ceRNA) networks were constructed by prediction software TargetScan & miRanda.Results: Many mRNAs were significantly differentially expressed between nevus sebaceous and adjacent normal scalp tissues. Among them, 72 were upregulated and 18 were downregulated. KEGG pathway analysis further revealed that 32 functional pathways were associated with the upregulated mRNAs, while only 1 pathway was associated with the downregulated mRNAs. Verification by real-time PCR and Western blot indicated that CDKN2AIP gene was downregulated consistently in NS tissue compared to normal scalp skin. Additionally, 7 upregulated and 10 downregulated significantly differentially expressed lncRNAs were detected between NS and adjacent normal scalp tissues. Three downregulated lncRNAs including AL355607.2, RP5-1024G6.8 and AC007780.1 were predicted to consistently associate with CDKN2AIP expression by competing endogenous RNAs(ceRNA) construction.Conclusion: Both mRNA and lncRNA profiles were altered in NS scalp tissues. We identified a downregulated gene, CDKN2AIP, as a target of differentially expressed mRNA and predicted a ceRNA network of CDKN2AIP with differentially expressed lncRNA.Keywords: nevus sebaceous, long noncoding RNA, ceRNA network, CDKN2AIP, wnt/β-catenin pathway